(untitled) (The Pakistan Development Review, 2013)
The finance-growth nexus has become a significant issue in recent macroeconomic modelling and the centre of attention of policy makers. Over the past few decades equity markets have experienced phenomenal growth which has proved to be a major determinant of capital flow to emerging market economies. Naturally, one wants to know how development of equity markets influences the real sector and produces macroeconomic outcomes. In this paper we construct an open economy, structuralist model to examine the short-run and long- run effects of both policy-induced and exogenous shocks on output, the dynamics of stock market valuation and adjustment in monetary base. The model shows that devaluation or capital inflow will boost the economy, while fiscal expansion has deleterious consequences for stock market valuation and investment. JEL Classifications: G01, G12, F32, F36 Keywords: Tobin’s q, Effective Demand, Devaluation